THE CONTRIBUTIONS OF SCHOOL PHYSICAL EDUCATION FROM A CRITICAL PEDAGOGICAL APPROACH - Dias, Flávia Hissamura; Derisso, José Luis [UNESP] (My University, 2024)
This study aimed to analyze the impact of morality and stereotypes on body formation, as well as the opportunities for intervention of school physical education from a critical pedagogical approach. The research path was outlined based on a qualitative and interpretative approach, through bibliographical review and critical analysis in which we sought to understand historically accumulated conceptions of the body, as well as the concept of body presented in school Physical Education in different pedagogical approaches. Finally, the research presents reflections and suggests possibilities for a meaningful work on the body through school physical education classes, based on the pedagogical approach of Historical-Critical Pedagogy and Historical-Cultural Psychology, which allow for an approach to the body in its entirety related to the bodily culture of physical education.
O PAPEL DA EDUCAÇÃO FÍSICA ESCOLAR NA REFLEXÃO CRÍTICA DO CORPO
Keywords: body; Historical-Critical Pedagogy; School Physical Education